Comprehensive therapies for severe facial pain related to temporomandibular disorder in a patient with mental instability - Huri, Stevani Gracela; Ismiyati, Titik; Barunawati, Sri Budi; Alhasyimi, Ananto Ali; Ruspita, Intan (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
The etiology of temporomandibular disorders (TMDs) is multifactorial and often associated with biopsychosocial factors. Stress, anxiety, and depression contribute to the psychological conditions that may accompany TMD. This case study aims to describe the treatment of severe facial pain associated with TMD in a patient experiencing mental instability. A 28-year-old female presented to a dental hospital with severe pain in the right facial region. The patient had previously worn a stabilizing occlusal splint six months prior, but had since lost it, resulting in the recurrence of pain. The pain originated in the right temporomandibular joint and radiated to the ear, eye, and temporal region. The pain was exacerbated by mouth opening, chewing hard food, and emotional stress. Clinical examination revealed missing lower first molars and an anterior crossbite. The patient reported frequent clenching episodes during periods of anxiety and depression. A panoramic radiograph showed both condyles to be normal in shape and size. A transcranial X-ray revealed the right condyle positioned within the glenoid fossa, while the left condyle was located anterior and inferior to the articular eminence. Treatment included a comprehensive approach: pharmacologic therapy, elimination of parafunctional habits, self-management strategies, a stabilizing splint, partial dentures, psychiatric intervention, and orthodontic treatment. The masticatory muscles showed significant relaxation following treatment, resulting in pain reduction. Orthodontic correction of the malocclusion and increased vertical dimension of occlusion led to improved quality of life and the resolution of TMJ symptoms.